Selaginella chrysorrhizos (Selaginellaceae), a new addition to the lycophyte flora of China based on morphological and molecular evidence - Huang, Jun-Kai; Xie, Zhi; Li, Xiao-Ji; He, De-Ming; Dong, Shi-Yong (Phytotaxa, 2026)
The identification of Selaginella leptophylla, a lycophyte species recorded from Guangdong and Hong Kong in southern China, is reviewed. Through literature review and specimen examination, we conclude that the record for S. leptophylla from Hong Kong is dubious due to the absence of authentic voucher specimens, whereas its record from Guangdong resulted from misidentification of S. chrysorrhizos, a species previously known only from the Eastern Himalayas and Indochina. This species has also been recently found in the wild in Yunnan and Xizang, southwestern China. Phylogenetic analyses of three plastid regions (rbcL, atpI, and psbA) demonstrate that S. chrysorrhizos is most closely related to S. densiciliata, S. vaginata, and S. xipholepis. A detailed description, along with illustrations, the diagnostic characters, and the morphological comparisons with similar species, is provided for S. chrysorrhizos.